2017
DOI: 10.1016/j.ydbio.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

The TEAD family transcription factor Scalloped regulates blood progenitor maintenance and proliferation in Drosophila through PDGF/VEGFR receptor (Pvr) signaling

Abstract: The Drosophila lymph gland is a well-characterized hematopoietic organ in which a population of multipotent stem-like progenitors is maintained by a combination of signals from different cellular populations within the organ. The lymph gland serves as an ideal model both for the interrogation of signaling mechanisms involved in progenitor maintenance as well as a tool for the identification of novel regulatory mechanisms in the highly conserved process of hematopoiesis. Here, we demonstrate a requirement for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…Detailed temporal analysis of the dynamics of progenitor subpopulation during normal development, as well as upon loss of whd 1 ( Figure 2J–S ), was next carried out. In sync with an earlier report ( Ferguson and Martinez-Agosto, 2017 ), our analysis reveals that Dome - pre-progenitors ( Figure 2K ) are present in the developing lymph gland until the early third instar ( Figure 2L and Figure 2—figure supplement 1B ). Beyond this timeline, the subsets that populates the lymph gland are Dome + progenitors ( Figure 2M–N and Figure 2—figure supplement 1B ), and Dome + Pxn + IP cells ( Figure 2M–N and Figure 2—figure supplement 1B ).…”
Section: Resultssupporting
confidence: 91%
“…Detailed temporal analysis of the dynamics of progenitor subpopulation during normal development, as well as upon loss of whd 1 ( Figure 2J–S ), was next carried out. In sync with an earlier report ( Ferguson and Martinez-Agosto, 2017 ), our analysis reveals that Dome - pre-progenitors ( Figure 2K ) are present in the developing lymph gland until the early third instar ( Figure 2L and Figure 2—figure supplement 1B ). Beyond this timeline, the subsets that populates the lymph gland are Dome + progenitors ( Figure 2M–N and Figure 2—figure supplement 1B ), and Dome + Pxn + IP cells ( Figure 2M–N and Figure 2—figure supplement 1B ).…”
Section: Resultssupporting
confidence: 91%
“…Discovery of the hidden cell population-PH1, will shed light on understanding the hierarchy of prohemocyte differentiation and enhance the relevance of the lymph gland as a hematopoietic model. Roles for Notch, Stat92E, or scalloped in the earliest state of prohemocytes have been previously suggested by recent studies 18,[48][49][50] . Moreover, clonal analyses have shown that cells adjacent to the PSC generate the largest population in the lymph gland 51 .…”
Section: Discussionmentioning
confidence: 69%
“…In Drosophila , sd mutants exhibit abnormal wings with wing margin gaps and ectopic bristles (Kiso, ; Campbell et al ., ; Campbell et al ., ). sd overexpression promotes tissue overgrowth, while sd inactivation decreases organ size, including neuroblasts, brain, eyes, and wing discs in Drosophila melanogaster (Poon et al ., ; Boone et al ., ; Ferguson & Martinez‐Agosto, ). Additionally, sd affects the development of various Drosophila organs, such as the eyes, legs, optic lobe (Garg et al ., ), sensory bristles (Anand et al ., ), trachea (Robbins et al ., ), and lymph glands (Ferguson & Martinez‐Agosto, , ).…”
Section: Introductionmentioning
confidence: 99%